IMPLEMENTASI E-GOVERNMENT MELALUI APLIKASI DEPOK SINGLE WINDOW DI KOTA DEPOK - Indriasari, Ratna; Prakosa, Alfriza Nadindra (Jurnal Wahana Bina Pemerintahan, 2023)
The Depok City Government responded to advances in information technology by launching an e-app. Government application, Depok Single Window (DSW), in August 2018. Despite its potential to improve public services, DSW faces several obstacles such as lack of evaluation, decline in users, unpreparedness in handling complaints, and lack of socialization. This research aims to find out the Implementation of e-government in improving public services through the Depok Single Window application in Depok City, Furthermore, to find out the supporting factors and inhibiting factors in the implementation of e-government. supporting factors and inhibiting factors in the implementation of e-government through the Depok Single Window application in Depok City, and to find out the efforts of the Depok City government in improving the implementation of e-government through the Depok Single Window application. Depok Single Window application. This research uses a qualitative method with a descriptive approach, focusing on the Depok City Communication and Informatics Office. Communication and Informatics Office of Depok City. Data collection was done through interviews, observation, and documentation. Data analysis techniques with data reduction, data presentation, conclusion drawing, and verification. verification. The results showed that First, the Depok City Government continues to innovate by implementing e-Government through the "Depok Single Window" application. implementation of e-Government through the "Depok Single Window" application. access to public services, provide efficient solutions, and is expected to improve the quality of services. service. This progressive step is expected to make a positive contribution to the overall development of Depok City. Depok City as a whole. second, supporting factors for the implementation of e-government policies are rules that all existing public service applications in the regional apparatus become one in the Depok Single Window application. Depok Single Window, the inhibiting factor is that there is no standardization of SOPs and technical policies supporting the service. the service. Third, the Depok City Government can improve the implementation of eGovernment implementation by organizing socialization, meetings between regional apparatus to discuss applications or features of online public services, and periodic internal evaluations. online public services and periodic internal evaluations are carried out to improve the quality of e-Government implementation. implementation of e-Government.